2021
DOI: 10.21203/rs.3.rs-189644/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association of Serum Vitamin D Status with gestational diabetes mellitus and other laboratory parameters in early pregnant women

Abstract: Background: Pregnant women develop certain metabolic alterations and substantial nutrient insufficiency, which may impact fetus development. Reports on the association of serum 25-hydroxy vitamin D (25(OH)D, VD) status with gestational diabetes mellitus (GDM) is still controversial. This study aimed to investigate the association of serum VD status with GDM and other laboratory parameters in early pregnant women.Methods: A total of 1516 pregnant women were enrolled in this study. Maternal serum VD and other la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Studies [11,12] have shown that vitamin D, as a micronutrient, has a certain correlation with GDM and various adverse maternal and infant outcomes. Studies [13,14] have shown that in order to maintain the growth of fetal bones during pregnancy, the consumption of vitamin D in pregnant women increases signifcantly, which can lead to general insufciency or even defciency of vitamin D in women after pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Studies [11,12] have shown that vitamin D, as a micronutrient, has a certain correlation with GDM and various adverse maternal and infant outcomes. Studies [13,14] have shown that in order to maintain the growth of fetal bones during pregnancy, the consumption of vitamin D in pregnant women increases signifcantly, which can lead to general insufciency or even defciency of vitamin D in women after pregnancy.…”
Section: Introductionmentioning
confidence: 99%